2007
DOI: 10.3354/ame047037
|View full text |Cite
|
Sign up to set email alerts
|

Morphological diversity of virus-like particles within the surface microlayer of scleractinian corals

Abstract: Transmission electron microscopy was employed to determine the morphological diversity of virus-like particles (VLPs) associated with the coral surface microlayer (CSM) of Acropora muricata and Porites spp. from the Great Barrier Reef, Australia. VLPs were assigned to one of 17 sub-groups within 5 major morphological groups including tailed bacteriophages, polyhedral, filamentous and lemon-shaped VLPs. Polyhedral VLPs in the 30 to 60 nm size class dominated the CSM of A. muricata and Porites spp., comprising 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
90
2
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(105 citation statements)
references
References 49 publications
11
90
2
2
Order By: Relevance
“…In addition to our datasets, transmission electron micrographs (TEM) and sequences from the Nematostella genome and hydra EST project provide further evidence that Cnidarians, not just corals, are hosts for herpes-like viruses. Corals contain large enveloped icosahedral virions morphologically similar to the Herpesviridae (28,29). Herpesvirus essential genes are also present in Cnidarian genomes (28,51,52).…”
Section: Additional Evidence For Herpes-like Viruses In Corals and Almentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to our datasets, transmission electron micrographs (TEM) and sequences from the Nematostella genome and hydra EST project provide further evidence that Cnidarians, not just corals, are hosts for herpes-like viruses. Corals contain large enveloped icosahedral virions morphologically similar to the Herpesviridae (28,29). Herpesvirus essential genes are also present in Cnidarian genomes (28,51,52).…”
Section: Additional Evidence For Herpes-like Viruses In Corals and Almentioning
confidence: 99%
“…Corals contain large enveloped icosahedral virions morphologically similar to the Herpesviridae (28,29). Herpesvirus essential genes are also present in Cnidarian genomes (28,51,52). Within the Nematostella draft genome, alkaline exonucleases, herpes major outer envelope proteins, herpes DNA primases, herpes ubiquitin-specific proteases as well a herpes surface glycoprotein and transcription activation factor were identified (Table S4).…”
Section: Additional Evidence For Herpes-like Viruses In Corals and Almentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, ) from different oligotrophic and eutrophic marine environments. FCM = flow cytometry; TEM = transmission electron microscopy; ND = not determined detachment of reef and coral surface-associated VLPs (Davy & Patten 2007) when water is advected through the reef framework may have indirectly contributed to increased water column viral loads. In contrast, bacterial abundances appeared to be less affected by tidal flushing and more responsive to the input of labile organic matter from the spawning event.…”
Section: Water Columnmentioning
confidence: 99%
“…Wilson et al, 2005;Danovaro et al, 2008) and lytic phages of coral pathogens have been isolated (Efrony et al, 2007). The morphological diversity of viruses in coral mucus and in the holobiont is high (Davy and Patten, 2007;Patten et al, 2008a) and a high diversity was also shown by viral metagenomics of the holobiont (Marhaver et al, 2008). There is also some in situ evidence that viral abundance increases close to corals (Patten et al, 2006;Seymour et al, 2005).…”
Section: Introductionmentioning
confidence: 99%